CALCIUM HYDROXYAPATITE SUPPORTED COBALT CATALYSTS FOR ETHANOL STEAM REFORMING: EFFECT OF THE INCORPORATION METHOD OF ACTIVE PHASE - DOBOSZ, Justyna; HULL, Sylwia; ZAWADZKI, Mirosław (Studia Universitatis Babeș-Bolyai Chemia, 2018)
Cobalt catalysts supported on calcium hydroxyapatite (Ca10(PO4)6(OH)2, HAp) and modified with cerium ions, were prepared in two different ways: direct microwave-assisted hydrothermal synthesis or incipient wetness impregnation method and characterized by XRD, TEM, SEM/EDS, FT-IR and Raman spectroscopy, N2 adsorption–desorption, TPD–NH3, TPR–H2 and XPS. The results indicate that Ca2+ ions in the hydroxyapatite lattice are substituted by Co2+ and Ce3+ under hydrothermal conditions while cobalt and cerium species are formed on the HAp surface during support impregnation. Catalytic activity of samples was tested for hydrogen production via ethanol steam reforming (SRE), and it was found that the highest hydrogen yield (over 3,5 mol H2/mol C2H5OH) and the best distribution of products were obtained for the catalyst prepared by the incipient wetness impregnation method. For this catalyst, Co species formed on the HAp surface was easier reducible than Co2+ ions located in the HAp crystal lattice, and surface was characterized by lower acidity.